BlueCarbon in National Policy to Reduce Green house Gas Emissions - Diah Apriani Atika Sari; Okid Parama Astirin; Anti Mayastuti; Anugrah Adiastuti (Yustisia, 2021)
Greenhouse Gas (GHG) emissions are the main cause of global warming and climate change. Indonesia as an archipelagic country experiences a significant negative impact as a result of climate change, such as sea level rise, sea water intrusion to the land, extreme weather, and rising sea and land temperatures. Tropical forests have been known as a major carbon emitter, but with the increasing rate of deforestation, it is necessary to find carbon sinks from ecosystems other than tropical forests. This study aimed to determine the extent to which blue carbon has been included in Indonesian Government policies, especially in the GHG inventory document and the Indonesian Nationally Determined Contribution (NDC) document, related to the Government of Indonesia's commitment in reducing GHG emissions. The research showed that blue carbon ecosystems, which include mangroves, seagrass beds, and other coastal ecosystems, have enormous carbon sequestration potential when compared to tropical forests, but unfortunately, the potential of blue carbon has not been maximally utilized in national policies related to GHG emission reduction. The existing policies have not been implemented optimally and some of them overlap. In the future, accurate data updating and mapping of the blue carbon ecosystem is needed so that it can become a reference in determining national policies on the use of blue carbon